Krasznojarszk, 1919. augusztus 1-2. - Takács, Gyula (Közép-Európai Közlemények, 2012)
On 1st and 2nd August 1919 the military court of the 12th Rifle Regiment of the Czech Legion sentenced to death 17 Hungarian prisoners of war in Eastern Siberia, who were executed in the military camp near Krasnoyarsk. As members of the Hungarian Alliance, five of them were accused of political conspiracy against the Czechoslovak state and hostile intentions against the Czech Legion. The accusation against three indictees was supporting rebel soldiers and nine persons were executed as former red guardist. This article summarizes the events and circumstances of the last days of July in the prisoners of war camp. It tries to find the prelude of this unfortunate case. It also gives some information about memoirs of witnesses and mentions the conditions within the camp. This article is only a brief overview of the issue based on some secondary sources. It is an edited variant of a conference lecture.